Virucidal and cytotoxic properties of a natural honeybee hives-derived formulation suspended with marine plasma - Bażanów, Barbara; Migdał, Paweł; Chwirot, Aleksandra; Kublicka, Agata; Gębarowski, Tomasz; Chorbiński, Paweł; Vogt, Andrzej; Szumny, Antoni; Kaczmar, Ewa; Michalczyk, Katarzyna; Stygar, Dominika (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionEmerging viral pathogens continue to pose serious threats to global health, prompting the search for novel antiviral agents derived from natural sources. Bee-derived products, particularly those enriched with lysozyme, have shown promising antimicrobial properties. This study aimed to evaluate the virucidal and cytotoxic properties of a new formulation combining extract from bee brood caps (EBBC) and enhanced marine plasma as a potential broad-spectrum antiviral agent.MethodsThe chemical composition of EBBC was characterized by gas chromatography–mass spectrometry (GC–MS) and lysozyme activity assays. Cytotoxicity was assessed using the sulforhodamine B (SRB) assay on normal epithelial (CCD841) and fibroblast (NHDF) cell lines. Virucidal activity was tested according to European (PN-EN 14476+A2:2019-08) and ISO (ISO 18184) standards. Additionally, the effect of EBBC on viral entry was analyzed using fluorescence microscopy.ResultsEBBC demonstrated potent virucidal activity, achieving ≥99.99% efficacy at concentrations as low as 0.01% and maintaining full effectiveness after 12 months of storage. The formulation was active against all tested viruses. Cytotoxicity testing revealed minimal toxicity, with concentration-dependent inhibition of epithelial cell growth and stimulation of fibroblast proliferation.DiscussionEBBC exhibits strong and stable antiviral activity at low concentrations with minimal cytotoxic effects. Its unique combination of bee brood cap extract and enhanced marine plasma suggests potential for development as a natural, broad-spectrum antiviral formulation, offering an alternative to conventional antiviral agents.